16S rRNA and metabolomics reveal the key microbes and key metabolites that regulate diarrhea in Holstein male calves - Cao, P. P.; Hu, C. L.; Li, M. J.; An, Y. H.; Feng, X.; Ma, X. H.; Wang, D. Z.; Song, Z. H.; Ji, G. S.; Yang, D.; Ma, Q.; Yang, W. F.; et al. (Frontiers in Microbiology, 2025)
IntroductionDiarrhea is a prevalent disease among calves, which significantly hinders their growth and development, thereby impacting farm productivity and revenue. This study aimed to investigate the impact of diarrhea on calf growth.MethodsHolstein male calves with similar birth weight (39.5 ± 4.2 kg) were included in this study, and key parameters such as fecal score, diarrhea incidence, and growth performance from birth to weaning were measured. Rectal fecal samples from both diarrheic (n = 24) and healthy calves (n = 24) aged 1–4 weeks were analyzed using 16S rRNA gene sequencing and untargeted metabolomics.ResultsOur findings indicated a high prevalence of diarrhea among calves between 1–4 weeks of age on pasture, which led to a marked decrease in growth performance, including average daily gain. At the genus level, the relative abundance of GCA-900066575 in one-week-old diarrheic calves was significantly higher; Escherichia-Shigella and Pseudoflavonifractor were more abundant in two-week-old calves; while Tyzzerella and Lachnospiraceae_UCG-004 increased significantly in four-week-old calves, and correlated negatively with average daily gain, suggesting that these bacteria may promote the occurrence of diarrhea. Correlation analysis revealed that fecal metabolites such as arachidonic acid, cis-vaccenic acid, oleic acid, choline, creatinine, and others were significantly negatively correlated with calf growth performance and were significantly increased in diarrheic calves. WGNCA identified that dark magenta module metabolites were significantly associated with diarrhea traits from 1–4 weeks. Thirteen metabolites, including glycerophospholipids (such as 1-stearoyl-2-hydroxy-sn-glycero-3-phosphoethanolamine), fatty acids (such as dodecanoic acid), and arachidonic acid, were positively correlated with GCA-900066575, Escherichia-shigella, Tyzzerella, and Clostridium_butyricum, but negatively correlated with UBA1819, Lachnoclostridium_sp_YL32, and Clostridium_scindens.DiscussionTherefore, GCA-900066575, Escherichia-shigella, Lachnospiraceae_UCG-004, and Tyzzerella are likely key bacterial genera causing diarrhea in calves, while arachidonic acid, glycerol phospholipids, and fatty acids are critical metabolites associated with this condition. These alterations in the fecal microbiota and metabolite composition were found to be the principal contributors to growth retardation in diarrheic calves.